2013
DOI: 10.1371/journal.pone.0053168
|View full text |Cite
|
Sign up to set email alerts
|

The Sesquiterpene Lactone Dehydroleucodine Triggers Senescence and Apoptosis in Association with Accumulation of DNA Damage Markers

Abstract: Sesquiterpene lactones (SLs) are plant-derived compounds that display anti-cancer effects. Some SLs derivatives have a marked killing effect on cancer cells and have therefore reached clinical trials. Little is known regarding the mechanism of action of SLs. We studied the responses of human cancer cells exposed to various concentrations of dehydroleucodine (DhL), a SL of the guaianolide group isolated and purified from Artemisia douglasiana (Besser), a medicinal herb that is commonly used in Argentina. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…HeLa cells treated with DhL show increased focal organization of DNA-damage sensors (c-H2AX and 53BP1) in addition to increased levels and activity of p53. It has been proposed, that the apoptosis induced by DhL might be preceded by a failure to progress normally through the cell cycle in cells with high levels of damaged DNA (Costantino et al 2013). Similarly, here we show that DhL induces cell death, DNA damage, PS exposure and morphological features compatible with programmed cell death in both replicative epimastigote and non-replicative trypomastigote forms of the parasite.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…HeLa cells treated with DhL show increased focal organization of DNA-damage sensors (c-H2AX and 53BP1) in addition to increased levels and activity of p53. It has been proposed, that the apoptosis induced by DhL might be preceded by a failure to progress normally through the cell cycle in cells with high levels of damaged DNA (Costantino et al 2013). Similarly, here we show that DhL induces cell death, DNA damage, PS exposure and morphological features compatible with programmed cell death in both replicative epimastigote and non-replicative trypomastigote forms of the parasite.…”
Section: Discussionsupporting
confidence: 84%
“…STLs are a large and structurally diverse group of plant metabolites; many members of which display anti-tumor effects (Costantino et al 2013) and anti-protozoan activities, among others (Amorim et al 2013;Barrera et al 2008;Jimenez-Ortiz et al 2005;Saeidnia et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that dehydroleucodine inhibited the degranulation of human leukemic LAD2 mast cells, thus acting as mast cell stabilizers (Vera et al 2012). Interestingly, it was reported that dehydroleucodine-treated cervical cancer HeLa cells became apoptotic, where the greater accumulation of DNA lesions that triggered the activation of ATM were consequently leading to transient G2/M arrest and permanent G1 arrest of HeLa cells (Costantino et al 2013).…”
Section: Artemisia Douglasianamentioning
confidence: 99%
“…Accordingly, we aim to discuss a list of phytonutrients reported to be involved in the induction of cell cycle arrest. Following certain natural agents, normal ATM function commonly triggers G1 arrest (Costantino et al 2013;Neumann et al 2014) via p53. ATM is also involved in inducing S phase (Tyagi et al 2005) and G2/M phase arrest (Guo et al 2014b;Tyagi et al 2014b).…”
Section: Introductionmentioning
confidence: 99%